2021
DOI: 10.1002/tox.23382
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to ammonia induces oxidative stress and enhanced glycolysis in lung of piglets

Abstract: Ammonia is one of the major environmental pollutants in the pig industry that seriously affects the airway health of pigs. In this study, we aimed to investigate the metabolic profiling changes of piglets’ lung tissue after the exposure of 0 ppm (CG), 20 ppm (LG) and 50 ppm (HG) ammonia for 30 days. Compared with the control group, the obvious lung lesions were observed in HG, including interstitial thickening, inflammatory cell infiltration and focal hemorrhage. The significantly increased content of malondia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Previous studies have demonstrated that ammonia exposure results in perturbations of amino acids, nucleotides, energy, and lipid metabolism in animals (Dong et al, 2020;Tang et al, 2020;Qin et al, 2022). We have consistently found that tyrosine metabolism, arginine and proline metabolism, pyrimidine metabolism, purine metabolism, citrate cycle (TCA cycle), glycolysis/gluconeogenesis, pentose phosphate pathway, and glycerolipid metabolism were influenced by house ammonia exposure (Figure 7).…”
Section: Ammonia Exposure Interferes With the Muscular Metabolic Profilesupporting
confidence: 59%
“…Previous studies have demonstrated that ammonia exposure results in perturbations of amino acids, nucleotides, energy, and lipid metabolism in animals (Dong et al, 2020;Tang et al, 2020;Qin et al, 2022). We have consistently found that tyrosine metabolism, arginine and proline metabolism, pyrimidine metabolism, purine metabolism, citrate cycle (TCA cycle), glycolysis/gluconeogenesis, pentose phosphate pathway, and glycerolipid metabolism were influenced by house ammonia exposure (Figure 7).…”
Section: Ammonia Exposure Interferes With the Muscular Metabolic Profilesupporting
confidence: 59%
“…To this end, MSEW did cause a significant reduction in 1-monopalmitin hippocampal levels in FSL rats (Table 3). 1-Monopalmitin is a lipid responsible for amongst others, storing energy and acting as a structural component of cell membranes (Qin et al, 2021). Consequently, that MSEW induced a reduction in hippocampal 1-monopalmitin of FSL rats (Table 3) could suggest a negative effect on mitochondrial function and is strongly supported by the robust preoteomics analysis of Mallei et al (2015) on the Flinders strain and recent findings linking stress-related pathways, stress reactivity and the effects on mitochondrial function (Rappeneau et al, 2023).…”
Section: The Effect Of An Early-life Stressor On Bio-behavioural Para...mentioning
confidence: 78%
“…Ammonia stress also causes changes in energy metabolism in animals. For example, pigs exposed to chronic ammonia stress activated glycolysis and lipolysis in the lungs 13 . Aquatic organisms exposed to stress also adaptively change metabolism of energy yielding nutrients such as glucose and lipids 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, pigs exposed to chronic ammonia stress activated glycolysis and lipolysis in the lungs. 13 Aquatic organisms exposed to stress also adaptively change metabolism of energy yielding nutrients such as glucose and lipids. 14,15 For instance, ammonia exposure reduced lipogenic enzymes fatty acid synthase (FAS) and 6-phosphogluconate dehydrogenase (6PGD) activities in juvenile yellow catfish (Pelteobagrus fulvidraco) and induced lipid decomposition in pacific white shrimp (Litopenaeus vannamei).…”
mentioning
confidence: 99%